Humanitarian competencies of a doctor (cardiologist) - E. O. Taratukhin (Российский кардиологический журнал, 2019)
The article reveals the features of working with the patient as a social and psychological subject, who, in addition to somatic pathology, has an experience of the disease situation. Psychosocial risk factors for cardiovascular (and more generally non-infectious) pathology, as well as social well-being as a component of positive health, are considered as elements of a doctor-patient relationship. Work with a person requires from a doctor competency that differs from working with pathology at a biological level. Perhaps, the time has come to single out “biomedical doctors” and “medical doctors” in clinical medicine, of which the first ones are not required humanitarian competencies. Since non-infectious pathology largely includes psychosomatic features, and mental processes are filled with an experience of social reality, the clinician must have skills of human sciences to work with them. This is especially important in view of the physician’s power as an ambassador of medicine and health. The following competencies are discussed: internal work skills, situational search and interpretation, communicative and ethical competence, development of positive health.